Impact of SARS-CoV-2-Pandemic on Mental Disorders and Quality of Life in Patients With Pulmonary Arterial Hypertension - Park, Da Hee; Fuge, Jan; Meltendorf, Tanja; Kahl, Kai G.; Richter, Manuel J.; Gall, Henning; Ghofrani, Hossein A.; Kamp, Jan C.; Hoeper, Marius M.; Olsson, Karen M. (Frontiers in Psychiatry, 2021)
Background/Objective: Covid-19 pandemic may affect mental health and quality of life (QoL) in patients with pulmonary arterial hypertension (PAH). We assessed changes in anxiety and depression, quality of life (QoL) and self-described impact of Covid-19 in patients with PAH during the Covid-19 pandemic. Methods: This study included 152 patients with PAH from two German referral centers. Anxiety and depression were assessed using the Hospital Anxiety and Depression Scale (HADS-A and HADS-D) at two different timepoints before and during the Covid-19 pandemic with a median of 232 days between baseline and follow-up. QoL was assessed using EQ-5D and emPHasis-10. Perceived impact of Covid-19 and related regulations and measures were assessed using a set of specific questions and statements. Results: More than two thirds of patients had an unsuspicious HADS-A and HADS-D. Median scores did not differ from baseline for both HADS-A and HADS-D (p=0.202; p=0.621). Overall, no significant changes in HADS-A or HADS-D categories from baseline to follow up were observed (p=0.07; p=0.13). QoL did not change between baseline and follow-up. The Covid-19 pandemic had little impact on access to medical care and established PAH therapy. Patients were in agreement with governmental measures and regulations and felt sufficiently safe. Conclusion: First waves of Covid-19 pandemic had little impact on anxiety, depression and QoL in patient with PAH. Established PAH therapy and access to medical care were not affected. Further studies on the impact of prolonged duration of the ongoing Covid-19 pandemic are needed.